Concep????o de criatividade na pr??tica de professores de arte de anos finais do ensino fundamental, em escolas particulares de Bras??lia - DF - Santos, Luciana Lopes Domingues dos (2013)
In this study, we investigated the conceptions of creativity presented by Art teachers and its impact in their pedagogical practice. We also analyzed some pedagogical procedures that can promote or inhibit the student???s creative potential as well as the evaluative practice used by the teachers in order to characterize their creative expression. Ten Art teachers working with the final grades in ten Elementary private schools in Brasilia DF participated in the study. We used the qualitative approach of descriptive-exploratory feature with semi-structured interviews as data input. There were descriptive questions about the concept of creativity, pedagogic procedures and evaluation criteria in order to qualify a piece of work as a creative one. The data was analyzed according to the content analysis proposed by Bardin. The results suggest that the teachers conceptions of creativity are guided by theoretical studies on the subject, anchored in the idea that the creative act is linked to personal attributes that lead to the production of a new product that is subject to the judgment of a particular medium. The importance of creativity was associated with the fact of being related to the life history of each individual and the resolution of a given problem. As to the practices that promote the creative potential, the results showed that motivational actions using instigating questions, diversified strategies, work of arts reading and analysis as well as offering diversified materials for exploration are common actions. As to the teacher???s posture, it was signaled as an element of the practice that can inhibit the development of creativity especially when the teacher criticizes the student??s work in a excessive way. In addition to the features and qualities of the teacher, were highlighted as potential obstacles environment too clean and organized and the students themselves. The study pointed out that the evaluation of the teacher???s creative process is under each teacher???s personal judgment associated to some parameters (aesthetic quality, observing the process), evaluative instruments (tests, practical work, activities) and the student???s participation.